2018
DOI: 10.1371/journal.pntd.0006998
|View full text |Cite|
|
Sign up to set email alerts
|

Trypanosoma cruzi-specific IFN-γ-producing cells in chronic Chagas disease associate with a functional IL-7/IL-7R axis

Abstract: BackgroundThe severity of cardiac disease in chronic Chagas disease patients is associated with different features of T-cell exhaustion. Here, we assessed whether the ability of T cells to secrete IFN-γ in response to T. cruzi was linked to disruption in immune homeostasis and inflammation in patients with chronic Chagas disease.Methodology/Principal findingsPBMCs from chronic Chagas disease patients and uninfected controls were examined for frequencies of T. cruzi-responsive IFN-γ-producing cells by ELISPOT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
2
11
1
Order By: Relevance
“…cruzi infection of mice, the deficiency of IL-27 or WSX-1 inhibited the control of parasite burden despite the elevated production of inflammatory cytokines [ 30 32 ]. Whereas previous findings of our group have shown decreased IL-27 serum levels in patients with no signs of cardiac dysfunction [ 14 ], other authors have reported increased levels of IL27p28 in these patients [ 32 ]. However, it is unknown whether the signaling pathway of IL-27/IL-27R is functional in the chronic phase of Chagas disease in humans.…”
Section: Introductioncontrasting
confidence: 80%
See 1 more Smart Citation
“…cruzi infection of mice, the deficiency of IL-27 or WSX-1 inhibited the control of parasite burden despite the elevated production of inflammatory cytokines [ 30 32 ]. Whereas previous findings of our group have shown decreased IL-27 serum levels in patients with no signs of cardiac dysfunction [ 14 ], other authors have reported increased levels of IL27p28 in these patients [ 32 ]. However, it is unknown whether the signaling pathway of IL-27/IL-27R is functional in the chronic phase of Chagas disease in humans.…”
Section: Introductioncontrasting
confidence: 80%
“…We have shown that the levels of IFN-γ-producing cells in response to T . cruzi antigens are positively associated with the expression and function of the receptor of homeostatic IL-7 in T cells and can be augmented after in vitro stimulation with IL-7 or IL-27 [ 14 ]. IL-27 can mediate the differentiation and proliferation of Th1 cells [ 15 ], activation of cytotoxic CD8 + T lymphocytes [ 16 ] and NK cells [ 17 ], and suppression of Th2 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1e). In addition, IL-7, a crucial cytokine for T-helper 1 responses [23][24][25][26] , was the most downregulated gene, with an~6-fold decrease in both types of patients.…”
Section: Immune Transcriptome Analysis Of the Ntm Patients And The Hcsmentioning
confidence: 99%
“…The serum levels of several cytokines, including IL-21, positively correlated with disease severity in patients with chronic Chagas disease caused by T. cruzi (Natale et al, 2018). Consistently, lower levels of IL-21 production were observed in the sera of human subjects with less severe cardiac dysfunction as compared with those presented with an advanced cardiac dysfunction profile (Natale et al, 2018). These observations may suggest a potential role for the IL-21/IL-21R axis in the promotion of pathology in chronically-infected human subjects.…”
Section: Protozoan Parasitesmentioning
confidence: 99%